A casa de Alice [videorecording (DVD)] = Alice's house - Teixeira, Chico; Ribas, Carla; Zemel, Berta; Zinn, Vinicius (FiGa Films, 2009)
Alice is a São Paulo manicurist, wife and mother of three sons who has a chance meeting with an old boyfriend. She is forced to re-examine her life and address her romantic dreams. In her quest for happiness, she must overcome the obstacles set by the male dominated world in which she feels trapped. Now, she must navigate the dangerous terrain of her heart.